Optimization of binderless compressed veneer panel manufacturing process from oil palm trunk using response surface methodology - Norhafizah, Saari; Junidah, Lamaming; Rokiah, Hashim; Othman, Sulaiman; Masatoshi, Sato; Arai, Takamitsu; Kosugi, Akihiko; Wan Noor Aidawati, Wan Nadhari (Elsevier Science, Ltd., 2020)
The aim of this study was to optimize the processing variables of producing compressed veneer panel from oil palm trunk without synthetic adhesive using response surface methodology. Based on the analysis, the optimal pressing temperature was at 186.6 °C and pressing time at 30 min and using outer part of oil palm trunk veneer to produce compressed veneer panel from oil palm trunk with acceptable mechanical strength and dimensional stability. The panel was produced by stacking 5 layers of 0.45 cm veneer to achieve final target thickness of 10 mm. The statistical analysis indicated that bending and shear block strength of the panel from optimal manufacturing condition were 36.07 MPa and 5.20 MPa respectively with 35.4% of delamination. It was shown that certain manufacturing parameters including pressing temperature, pressing time and part of oil palm trunk veneer could bind the oil palm trunk veneers without the need of synthetic adhesives with acceptable mechanical and physical properties.